2021
DOI: 10.1371/journal.pone.0257925
|View full text |Cite
|
Sign up to set email alerts
|

Combination of generalist predators, Nesidiocoris tenuis and Macrolophus pygmaeus, with a companion plant, Sesamum indicum: What benefit for biological control of Tuta absoluta?

Abstract: Tuta absoluta is one of the most damaging pests of tomato crops worldwide. Damage due to larvae may cause up to 100% loss of tomato production. Use of natural enemies to control the pest, notably predatory mirids such as Nesidiocoris tenuis and Macrolophus pygmaeus, is increasingly being promoted. However, considering the potential damage caused to tomatoes by these omnivorous predators in the absence of T. absoluta, an alternative solution could be required to reduce tomato damage and improve the predators’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…Nesidiocoris tenuis can reproduce on sesame in the absence of prey [ 40 ]. In cage studies, the combination of sesame and tomato increased N. tenuis populations without increasing damage to the tomatoes [ 17 , 28 , 31 ]. This study showed that the benefits previously seen with T. absoluta when mirids, N. tenuis and Macrolophus pygmaeus , were confined to a cage [ 31 ] could also work to control B. tabaci in open-field production where the mirids could leave the crop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesidiocoris tenuis can reproduce on sesame in the absence of prey [ 40 ]. In cage studies, the combination of sesame and tomato increased N. tenuis populations without increasing damage to the tomatoes [ 17 , 28 , 31 ]. This study showed that the benefits previously seen with T. absoluta when mirids, N. tenuis and Macrolophus pygmaeus , were confined to a cage [ 31 ] could also work to control B. tabaci in open-field production where the mirids could leave the crop.…”
Section: Discussionmentioning
confidence: 99%
“…In cage studies, the combination of sesame and tomato increased N. tenuis populations without increasing damage to the tomatoes [ 17 , 28 , 31 ]. This study showed that the benefits previously seen with T. absoluta when mirids, N. tenuis and Macrolophus pygmaeus , were confined to a cage [ 31 ] could also work to control B. tabaci in open-field production where the mirids could leave the crop. When given the ability to move freely in the field, N. tenuis did not remain on sesame despite the presence of whiteflies and being a better plant resource than tomato [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the key predators of T. absoluta are the zoophytophagous mirids such as Macrolophus pygmaeus (Hemiptera: Miridae), native to Europe and N. tenuis (Hemiptera: Miridae), native to the Mediterranean coast ( Sanchez et al., 2006 ; Sanchez et al., 2009 ; van Lenteren, 2012 ; Zappalà et al., 2013 ; Lins et al., 2014 ; Sanchez et al., 2018 ; Ayelo et al., 2021 ). For example, in a greenhouse tomato production study in Europe, M.pygmaeus was found to significantly reduced the population of whiteflies Bemisia tabaci and T. absoluta galleries ( Sanchez et al., 2018 ; Konan et al., 2021 ). These predators prey on eggs and lower instars of other small arthropods such as aphids, spider mites, and thrips ( van Lenteren, 2012 ; Zappalà et al., 2013 ; Sylla et al., 2016 ; Biondi et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…These predators prey on eggs and lower instars of other small arthropods such as aphids, spider mites, and thrips ( van Lenteren, 2012 ; Zappalà et al., 2013 ; Sylla et al., 2016 ; Biondi et al., 2018 ). In the absence of sufficient prey, they feed on leaf mesophylls, ground tissues of stems, inflorescences, and fruits of host plants resulting in significant yield reduction ( Moerkens et al., 2016 ; Sanchez et al., 2018 ; Konan et al., 2021 ). Previous studies have demonstrated that the availability of diverse food sources for generalist natural enemies in heterogeneous habitats reduced damage to host plants and attracted more predators compared to monocultures ( Tang et al., 2013 ; Grez et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%